Droughts, Dry Spells and Low Water Levels in Medieval Hungary (and Croatia) I: The Great Droughts of 1362, 1474, 1479, 1494 and 1507 - Kiss, Andrea; Nikolić, Zrinka (Journal of Environmental Geography, 2015)
In the present paper five significant late medieval drought events, occurred in Hungary (4 cases) and Croatia (1 Dalmatian case), are discussed based on contemporary documentary evidence. Information on long-term lack of precipitation, severe annual (or multiannual) water shortage, extreme low water levels of major rivers or bad harvest and severe food shortage in 1362, 1474, 1479, 1494 and 1507, often accompanied or followed by locust invasions, were documented both in narratives, account books, charters and letters. Apart from causing food shortage or difficulties in transportation (e.g. of salt), these greatest known documented drought events of medieval Hungary were blamed for weakening the country’s military defence (e.g. low water levels) and providing good opportunities for Ottoman-Turkish attacks. These great drought events sometimes occurred one year later than those of the neighbouring areas in Central Europe - a fact that can be probably explained by the bi- or multi-annual nature of dry spells (e.g. in and around 1474, 1479, 1507) that does not necessarily fit the frame of a calendar year.